THE USE OF BLOCK MEDIA IN CHILDREN AGED 4-5 YEARS IS INCREASING SKILLS FOR RECOGNIZING NUMBERS AND SIMPLE ADDITIONS - Juniaty, Juniaty; Linawati, Sri (Indonesian Journal of Early Childhood Education Studies, 2019)
Abstract. Learning media is very important to use in delivering learning material. Children age 4-5 years are in the Preoperational period, where children begin to think abstractly, but not logically, therefore children need learning media to understand abstract concepts such as numbers in mathematics. Blocks are one of the learning media available in schools, but not many teachers have used blocks media optimally, even though blocks can be used in mathematics learning. In the first semester, the understanding of numerical recognition and simple addition skills of K1 children in XYZ school were low. The researcher used blocks as the learning media in an effort to improve numerical recognition skills and simple addition. The research method used in the ?Classroom Action Research? is the Kemmis and Taggart model. The purpose of this study was to improve the ability to recognize numbers and simple addition of children 4-5 years, using blocks media in their learning. The Classroom Action Research conducted with three cycles showed an increase in numerical recognition skills from pre-cycle with a percentage of 61.45%, increasing to 89.76% in cycle III. Simple addition skills were known at the pre-cycle of 64.58%, increasing to 86.68% in cycle III. From the research conducted, the researcher found that blocks media can improve the skills of recognizing numbers and simple addition of children age 4-5 years.